A technology enhanced learning framework for enterprise performance optimisation - Brown, Liam (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2012)
Enterprise perfornnance optimisation is critical for organisations to survive and prosper in today's competitive global market-place. While this is true for all organisations, the need is even greater for the Small and Medium sized Enterprise (SME) sector. Effective enterprise performance optimisation requires the implementation of continuous improvement and change management programmes based on the Lean philosophy. Lean is a continuous improvement methodology' where waste is systematically identified and eliminated and value is created from the customer's perspective (Womack, 2011). Empowering employees at all levels throughout the organisation is central for the effective implementation of Lean. They must be equipped with the necessary knowledge, skills and tools to support enterprise performance optimisation endeavours. This thesis explores the potential of technology enhanced learning as an enabler of individual and organisational transformation through Lean thinking and thus enterprise performance optimisation. This thesis outlines how knowledge management, organisational learning, the learning organisation and continuous improvement methodologies including Lean are inter-related and how they contribute to organisational transformation and enterprise performance optimisation. Examples from both large enterprises and small and medium sized enterprises over the last number of decades are outlined and a comparative analysis between both sectors is undertaken.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.